Masampere: A Creative Process in Sangihe Community Post Zending Tukang - Latuni, Glenie; Utomo, Udi (Universitas Negeri Semarang, 2018)
This paper aims to explain the creative process of Masampere music post Zending Tukang from Germany in Sangihe in the late 20th century which influenced the singing culture of the Sangihe community. Using the concept of qualitative research based on a multidisciplinary approach complemented by the concepts of history, anthropology, sociology, and ethnomusicology, this study was used to solve problems through observation, interviews, and literature review and Masampere singing analysis in the community. The arrival of Zending Tukang in Sangihe aims to carry out evangelism through planting a lifestyle in the style of Pietism Calvinism so that the people of Sangihe can get out of traditional lifestyles into creative communities. Evangelism began with the establishment of a school (working stendent) called the Gunung school in Manganitu. Learning at the school was free, all students were trained to farm, work, sew, raise livestock, and trade by selling their work. Music is also the main subject in this school. Meistersinger German-style vocal music is applied by E.T. Steller with the concept of the rhythm pattern of proonos prootos in accapela singing. In addition, church schools also train students to sing. After that, a singing competition with awards and prizes was offered in the race. As a result, a form of singing art emerged with a new style in Sangihe, which was singing a choir in an acclaimed manner with the style of matunjuke, masampere, and mebawalase which the community called Masampere music.